Toward a discursive approach to growth models: Social blocs in the politics of digital transformation - Sidney A. Rothstein (Max Planck Institute for the Study of Societies, 2020)
The growth models perspective analyzes the role of social blocs in crafting countries' economic policies, but its treatment of business power as purely structural prevents it from addressing an important question in the politics of digital transformation: How have new sectors with miniscule economic footprints been able to influence economic policy? This paper explores how tech and venture capital successfully lobbied for financial deregulation at the beginning of digital transformation in the United States. The paper argues that explaining the role of social blocs in digital transformation requires incorporating discourse analysis and develops a conceptual framework around three discursive components in the dynamics of social blocs: coordination, persuasion, and performativity. This framework contributes to theory development in the growth models perspective and illustrates how the concept of social blocs can help make sense of the politics of digital transformation. – – Die Perspektive der Wachstumsmodelle analysiert die Rolle gesellschaftlicher Koalitionen bei der Festlegung der Wirtschaftspolitik der einzelnen Staaten. Ihre Behandlung der Unternehmensmacht als eine rein strukturelle verhindert jedoch, dass sie eine wichtige Frage in der Politik der digitalen Transformation angehen kann: Wie haben es neue Sektoren mit einem winzigen ökonomischen Fußabdruck vermocht, die Wirtschaftspolitik zu beeinflussen? Dieser Beitrag erörtert, wie Tech-Firmen und Risikokapitalunternehmen zu Beginn der digitalen Transformation in den USA erfolgreich für eine Deregulierung der Finanzmärkte lobbyiert haben. Er unterbreitet die These, dass die Erklärung der Funktion gesellschaftlicher Koalitionen für die digitale Transformation die Berücksichtigung der Diskursanalyse verlangt, und entwickelt einen begrifflichen Rahmen für drei diskursive Komponenten in der Dynamik gesellschaftlicher Koalitionen: Koordination, Überzeugung und Performativität. Dieser Rahmen trägt zur Theoriebildung in der Perspektive der Wachstumsmodelle bei und illustriert, wie der Begriff der gesellschaftlichen Koalition bei der Erhellung der Politik der digitalen Transformation helfen kann.
hdl:21.11116/0000-0006-8645-5
Keywords: 300; digital transformation; discourse; growth models; social blocs; digitale Transformation; Diskurs; gesellschaftliche Koalitionen; Wachstumsmodelle